Mendefinisikan Ulang dan Memperluas Domain Pengajaran dalam Program Persiapan Praktik Pembelajaran Calon Guru PAI di STIT Raden Wijaya Mojokerto - Padi, Achmad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
The paradoxical fact that education has become one of the main obstacles to intelligence and freedom of thought is lack of creativity in the education system. Creative pedagogy consists of three components: creative teaching, teaching for creativity and creative learning. Rapid developing domains that require teachers to keep abreast of developments, although both theory and realization of learning can be interpreted as creative actions, it is important to provide the same teacher constructive opportunities that we value for students, by avoiding the division of labor into 'theoretical' and those practical '(indeed, these are two activities that are not completely separate), and encourage agile adoption. In the Industry 4.0 era, humans and machines will work collaboratively using cognitive technology in the industrial environment. This scenario shows 21st century skills or lifelong learning competencies, including knowledge construction; adaptability; the ability to find, organize, and retrieve information; management; critical thinking; and teamwork. This is a PAI Teacher Candidate Learning practice program preparation at STIT Raden Wijaya Mojokerto? The results of discussion can be summarized as follows: 1) Developing a clear, practical approach to improving teacher skills and capacity for creativity in programs that present certain challenges. Integration of program architecture must be holistic in developing the creativity of prospective teachers; 2) Pedagogical practices that support and models creative thinking in a collaborative and supportive environment accelerating students' creative processes. The belief that creativity is the process of education is needed is very important for curriculum reform. The products of the creative process and processes are limited, because the prospective teachers cannot distinguish creative actions in the class and do not know the teachings of strategies.